The inclusion of de-oiled wet distillers grains in feedlot diets reduces the expression of lipogenic genes and fat content in Longissimus muscle from F1 Angus-Nellore cattle - Ferreira, Mateus S. [UNESP]; Tomaz, Lais A. [UNESP]; Niehues, Maria B. [UNESP]; Ladeira, Marcio M.; Curi, Rogerio A. [UNESP]; Chardulo, Luis A. [UNESP]; Baldassini, Welder A. [UNESP]; Martins, Cyntia L. [UNESP]; Arrigoni, Mario B. [UNESP]; Machado Neto, Otavio R. [UNESP] (Peerj Inc, 2019)
The inclusion of agro-industry by-products originated from corn ethanol production has increased in animal nutrition in Brazil, reducing formulation costs. In the literature, there is no consensus on how the high inclusion of de-oiled wet distillers grains can affect beef quality and the expression of lipogenic genes in Longissimus muscle. The aim of this study was to evaluate the effects of WDG in the diet of F1 Angus-Nellore cattle on meat quality characteristics, chemical composition and expression of genes involved in lipid metabolism. A hundred F1 Angus-Nellore bulls, with average initial body weight (BW) of 369.5 +/- 49 kg were used. The experiment was carried out in a randomized block design, and the animals were divided into two blocks (light and heavy) according to the initial body weight. The animals were fed diets containing levels of 0 (control), 15, 30 and 45% of WDG replacing dry corn and soybean meal. After 129 days of feedlot, the animals were slaughtered and samples of the longissimus thoracis (LT) muscle were collected for quality analyzes such as shear force (3, 10 and 17 aging days), color (luminosity, red, Chroma and Hue), cooking losses, pH and chemical composition (moisture, protein, lipids and ash contents). In addition, the expression of the PPAR alpha, PPAR gamma, SREBP-1c, SCD1, LPL, FABP4, FASN, ACOX, CPT2, GPX1 and ACACA genes was investigated in the LT muscle by real-time reverse transcription polymerase chain reaction (RT-PCR). Data were analyzed using polynomial contrasts (linear, quadratic and control vs. WDG). There was no interaction (P > 0.05) between aging times and the inclusion of WDG in the diets on the meat quality (pH, cooking losses, coloration and tenderness). However, diets with increasing levels of WDG caused a linear reduction (P = 0.01) in the intramuscular fat of LT. The lipogenic genes SCD1, PPAR gamma, FASN and CPT2 were less expressed (P < 0.05) in response to the indusion of WDG. These results suggest that the indusion of WDG reduced the expression of lipogenic genes and consequently the marbling of LT muscle without affecting tenderness (shear force) and meat color traits.
Keywords: Chemical composition; Meat science; Nutrigenomics; Metabolism; Marbling; Meat; Beef